(3GdJLOjO GdJfXjej defXeGJ GdJYdje aj GdbQf (B21 :s (3CdjGJ GdGYJeGO (B-(3GOGQI GdLhOI GdTGedI (B-(3GdJNWjW GdGSJQGJjLj (B/s - (3GdfLGQ, aQjOs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2007)
(3jJchf gPG GdcJGH ef (B4 (3CbSGe (B: (3EOGQI efXheGJ GdJYdje (B- (3GdJNWjW GdESJQGJjLj (B-(3EOGQI GdLhOI GdTGedI (B- (3EOGQI GdJZjQ hjTed cd bSe SdSdI GdaUhd GdeJJGdjI ZGdJj JgOa Edi JbOje ebJQGMGJ dJWhjQ efXheGJ GdJYdje GdMGdjI bHd GdLGeYj hjYQV aUhdg cGdJGdj JTNjU CReI GdJYdje GdeYGUQ , OhQ GdGOGQI aj GdJQHjI hGdJYdje ,CgejI GdegGQGJ GdJgNWjWjI aj GdJQHjI hGdJYdje , GdSdhc GdJfXjej GdJQHhj , GdJLOjO hGdJWhjQ GdJfXjej aj GdeOGQS hGdLGeYGJ , GdQDjI GdeSJbHdjI dbjGOGJ GdJYdje , GdJNWjW GdGSJQGJjLj GdJQHhj , GdJNWjW GdGJQGJjLj ddLGeYGJ , GdJYdje hGdJfejI GdeJhGUdI EOQGI HQGeL GdJWHjb GdJQHhj aj GdeSJbHd , EOQGI GdLhOI GdTGedI aj GdeOGQS EOGQI GdLhOI GdTGedI , GSJQGJjLjGJ GdJShjb GdLGeYj , GSJQGJjLjGJ JMOjK GdJYdje , eQGLYI Odjd GdGYJeGO hVeGf GdLhOI aj GdJdje GdYGdj(B.s
(3HjHdjhZQGajG U(B.661 (3; edGMb U(B.667s
Keywords: (3GdJNWjW GdGSJQGJjLjs; (3GdJNWjW GdJQHhjs; (3GdJYdjes; (3GdJYdje (B- (3GdEOGQI GdJYdjejIs; (3GdJYdje (B- (3GdJYdje (B- (3GdJWhjQ Gdegfis; (3GdJYdje GdLGeYjs